Characteristics of the Triassic Source Rocks of the Aitutu Formation in the (West) Timor Basin - Asep Kurnia Permana; Aries Kusworo; Andi Heri Prastian (Geological Agency, 2014)
DOI:10.17014/ijog.v1i3.192The Triassic rocks of the (West) Timor Basin have been identified that was mainly deposited in the marine environment. The fine grained clastics and carbonate rocks of this Triassic marine facies are considered to be the most promising source rocks potential in this basin. In this paper we present geochemical and petrographic data from outcrop samples of the Triassic carbonate Aitutu Formation, due to emphasized the organic maturation, kerogen type of the organic matter and the origin of the organic matter. A representative of selected sample were subjected to the Rock-Eval Pyrolisis, vitrinite reflectance and thermal alteration index, bitumen extraction, were analyzed on the GC-MS. The samples were collected from marine deposit of the Triassic Sequence. The TOC values of the analyzed sample range between rich and rich organic richness (0.51% - 9.16%, wt.%, TOC), which consists mainly of type II and III kerogen and the organic matter consider to be predominantly oil/gas prone and gas prone potential. The thermal maturity assessed from Tmax, TAI, and vitrinite reflectance shows an immature to early peak mature stage of the organic matter. The GC-MS analyses of the biomarkers indicate mainly the organic matter derived from mixed source rocks facies containing alga debris and higher plant terrestrial origin.